The development of driving school web based system with appointment notification via SMS / Fadhlil Syafiq Bahari - Bahari, Fadhlil Syafiq (2007)
“Driving School Notification System via SMS” is developed to reduce and ease current appointment notification difficulties in driving school system. Currently, student, instructor and the driving school communicate with one another via their respective handheld devices or face-to-face meet up to set their driving class appointment schedule. Other than that, instructor is not dealing with only one student but more. It can cause them difficulties in remembering all the schedule being set. To add to that problem, the appointment might change as needed according to the availability of both parties. These changes might possibly cause either side forgetting the appointment being set. With this system, Short Messaging System(SMS) is the method being use to set an appointment between the instructor and their student. SMS will be sent to list availability of the instructor and confirm the appointment. The instructor and student will be able to check their respective schedule from the SMS. SMS will also be sent to both parties reminding them about the appointment 1 or 2 days before. The use of SMS and the web-based system enable the driving school to record their employee appointment schedule properly. The resource for the developed system is collected from interviews, books, internet and previous related project being done. Developing the system required in depth studies in setting up SMS server and developing the web-base system. This is essential in enabling the communication between the driving school database and the student and instructor mobile devices. It is concluded that this system provided the decent solution for the current problem occur in the driving school system.